EXPERIENTIAL LEARNING MANAGEMENT USING EDUCATIONAL GAME FOR BASIC MATHEMATICAL SKILL DEVELOPMENT OF PRE-SCHOOL PUPILS OF ANONGNART KINDERGARTEN SCHOOL - Ratsirijan, Preechaphat; Wongsan, Weera; Somboon, Tanadol (Journal of Educational Review Faculty of Education in MCU, 2020)
The purposes of this research were 1) to develop basic mathematics skills of pre-school pupils of Anongnart Kindergarten before and after being engaged in experiential learning management using Snakes and Ladders’Game and 2) to compare the pupils’ knowledge of overall, the basic mathematics skills and basic mathematics of numbers 1-20, memorization of numbers 1-20, arrangement of numbers 1-20 and addition of numbers 1-20 after participating in experiential learning management using Snakes Game. By using the simple random sampling technique, the study sample were comprised of 16 pre-school pupils who were learning in Anongnart Kindergarten in the second semester of academic year 2019. The research instruments included experiential learning management plans containing learning activities based on Snakes Game and a test to evaluate the pupils’ mathematics knowledge. The statistics used for analyzing the collected data were percentage, mean, standard deviation and t-test. The research findings were as follows: 1) overall, the basic mathematics skills in knowledge after participating in experiential learning management using Snakes Game was at high. 2) the basic mathematics skills of total scores, the score of numbers 1-20, memorization of numbers 1-20 , arrangement of numbers 1-20 and addition of numbers 1-20 after participating in experiential learning management using Snakes Game was at high and 3) after being engaged in learning experience using Snakes Game, the pupils of Anongnart Kindergarten gained a higher level mean score of basic mathematics skills than they did before experimental teaching at the 0.05 level of significance.